Nilai Ekonomi Akibat Kerusakan Jalan Berdasarkan Pendekatan Willingness to Pay dan Willingness to Accept di Jalan Lintas Timur Sumatera - Anwar, Aditya (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2009)
Eastern Sumatera Highway plays an important role as economic pulse of Sumatera. This indicates that Eastern Sumatera Highway holds a high economic value for inhabitat of Sumatera island in particular as well as Indonesian society in general. Eastern Sumatera Highway conditions that are less solid resulted in lesser economic value of it. Methodology used in this study was quantitative. This study is expected to be in figuring the economic value of Eastern Sumatera Highway, as applied as beneficial input in determining suitable policy. Willingness to Pay (WTP) an Willingness to Accept (WTA) approach used in this study are proven to give well illistration of economic value of the impact caused by the destructed road based on testimony of surrounding society and highway user with various vehicles.